The Moderating Effect of Religious Involvement on the Relationship Between PTSD Symptoms and Physical Pain in U.S. Veterans and Active Duty Military. (3rd July 2019) - Lea, Christopher R.; Oliver, Rev. John P.; Smothers, Zachary; Boucher, Nathan A.; Youssef, Nagy A.; Ames, Donna; Volk, Fred; Teng, Ellen J.; Koenig, Harold G.
Abstract: The relationship between posttraumatic stress disorder (PTSD) symptom severity and pain is well known in veterans and active duty military (V/ADM). This study examines the buffering effect of religiosity on that relationship. A multisite study was conducted involving 585 V/ADM from across the United States. Multidimensional measures of religiosity, PTSD symptoms, depression/anxiety were administered, along with physical pain on a 0 to 10 visual analog scale. Bivariate and multivariate relationships were examined, along with the moderating effects of religiosity. PTSD symptoms were significantly related to pain level ( r = 0.44), a relationship that was only slightly weaker among highly religious ( r = 0.34) vs. nonhighly religious ( r = 0.48). In multivariate analyses, the interaction between religiosity and PTSD severity on pain was not significant, although stratified analyses indicated a somewhat weaker relationship between PTSD severity and pain in the highly religious (B = 0.03, SE =0.01, t = 2.28, p = 0.02) compared to those who were not (B = 0.06, SE =0.01, t = 6.55, p < 0.0001). Likewise, effects of pain on PTSD symptoms appeared weaker in the highly religious (B = 0.67, SE =0.37, t = 1.80, p = 0.07) compared to others (B = 1.32, SE =0.25, t = 5.34, p < 0.0001). Conclusion: This study provides only minimal evidence that high religious involvement may buffer the effects of PTSD symptoms on pain and vice-versa.